Implementar estrategias de comprensión lectora a través de un VLO para mejorar el nivel de inglés en el examen Saber 11 (2023)
In order to analyze the impact of implementing reading strategies through a Virtual Learning Object (VLO) to enhance the English comprehension level in the Saber 11 exam, it was necessary to base this research on recent data collected from the Instituto Colombiano para la Evaluación de la Educación (ICFES) and some research based on the application of digital resources in English classes, since all of them allowed to understand the importance of technology to increase student’s motivation in the presentation of reading comprehension exercises. In that sense, this study was conducted with an action research with a phenomenological philosophy and an exploratory approach, using mixed methods methodology where the data was collected, analyzed, and integrated both quantitative and qualitative research. The results showed that the change and help from this implementation was qualitative, regardless of certain quantitative findings observed in the Data Analysis that did not reveal a significant difference with the use of the VLO. However, students increased their interest and self-confidence by developing the talents and strengths that each of them possessed.